THE ROLE OF FINTECH APPLICATIONS IN IMPROVING INVESTMENT EASE IN INDONESIA - M. ILHAM TANJUNG (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2024)
The development of financial technology (fintech) in Indonesia has transformed how people invest by providing accessibility, transparency, and efficiency in digital financial management. This study aims to analyze the roles of two major fintech applications, Bibit and Indodax, in facilitating investment access and improving digital financial literacy among users. The research employed a literature review and descriptive observation method using data from the Financial Services Authority (OJK), Commodity Futures Trading Regulatory Agency (BAPPEBTI), academic publications, and official company reports. The results show that Bibit excels in user-friendliness and investment education, while Indodax emphasizes flexibility in crypto-asset trading. Both contribute positively to the expansion of digital financial inclusion, although they differ in risk levels. In conclusion, fintech-based investment platforms play a crucial role in promoting more inclusive, efficient, and secure investment practices, yet continuous financial literacy improvement is necessary to ensure responsible risk management among users.